Associations of impaired glucose tolerance and sleep disorders with mortality among the US general population. Issue 1 (5th August 2021) - Inoue, Kosuke; Semba, Eriko; Yamakawa, Tadashi; Terauchi, Yasuo
Abstract : Introduction: Sleep disorders and short sleep duration are common symptoms among people with diabetes. However, the evidence is limited about the associations of post-challenge hyperglycemia and sleep quality or quantity with all-cause mortality in the US general population. Research design and methods: Our study included 8795 adults from the National Health and Nutrition Examination Survey 2005–2014. Mortality data were ascertained through 2015. Multivariable Cox proportional-hazards models were used to estimate adjusted HRs (aHRs) for all-cause mortality according to 2-hour plasma glucose levels during the 75 g oral glucose tolerance test—normal glucose tolerance (NGT), <140 mg/dL; impaired glucose tolerance (IGT), 140–199 mg/dL; and diabetes, ≥200 mg/dL. We then examined the associations of glucose tolerance status and self-reported physician-diagnosed sleep disorders (yes vs no) or sleep duration (<7 vs ≥7 hours) with all-cause mortality. Results: During follow-up (median, 5.6 years), the diabetes group had a higher risk of all-cause mortality compared with the NGT group (aHR (95% CI)=1.93 (1.41 to 2.64)), but not the IGT group (aHR (95% CI)=1.19 (0.90 to 1.59)). When we categorized participants according to glucose tolerance status and sleep disorders, the IGT group with sleep disorders had a higher risk of all-cause mortality (aHR (95% CI)=2.03 (1.24 to 3.34)) compared with the NGT group without sleep disorders. Both diabetes groups with and without sleep disorders also showed high mortality risks. The results were consistent when we used sleep duration instead of sleep disorders. Conclusions: Using the most updated US national data, we found a high risk of all-cause mortality among individuals with IGT having sleep disorders or short sleep duration as well as those with diabetes. Future investigations are needed to identify whether and what kind of sleep management is beneficial for people with impaired glucose metabolism to prevent early death.